2015
DOI: 10.7150/ijms.10761
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Extracellular Matrix Scaffold Is a Multipotent Environment

Abstract: The multipotency of scaffolds is a new concept. Skeletal muscle acellular scaffolds (MAS) implanted at the interface of Tibialis Anterior/tibial bone and masseter muscle/mandible bone in a murine model were colonized by muscle cells near the host muscle and by bone-cartilaginous tissues near the host bone, thus highlighting the importance of the environment in directing cell homing and differentiation. These results unveil the multipotency of MAS and point to the potential of this new technique as a valuable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 15 publications
0
35
0
1
Order By: Relevance
“…Although the mechanisms are not yet fully understood, paracrine secreted cytokines and/or the extracellular matrix might affect the differentiation [ 11 ]. Muscle extracellular matrix scaffolds can recruit stem cells and induce differentiation, and this extracellular matrix scaffold promotes regeneration of other tissues such as bone cells depending on the surrounding environment [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms are not yet fully understood, paracrine secreted cytokines and/or the extracellular matrix might affect the differentiation [ 11 ]. Muscle extracellular matrix scaffolds can recruit stem cells and induce differentiation, and this extracellular matrix scaffold promotes regeneration of other tissues such as bone cells depending on the surrounding environment [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cell niche is a concept relatively new 18 and many authors have demonstrated that a scaffold can be multipotent 19 and can induce different phenotypes. On the other hand, cells can follow their own basal commitment 20 or they can be induced to differentiate into a phenotype definitely different from the biological niche where they were harvested.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, regenerative medicine issues have stimulated research to investigate an elevated number of new biomatrices 4 aimed at improving tissue healing; in this light, the old concept of bioscaffolds has given way to new concepts, such as acellular scaffolds, 5 cell niche, and cell commitment. [6][7][8][9][10] Regarding the scaffolds, the exposed surface area and porosity play major roles in the proliferative response of cultured cells. 11 Moreover, the architecture and the design of scaffolds have a clear effect on cells seeding and culturing.…”
Section: Discussionmentioning
confidence: 99%